The Effect of Excessive Use of Internet upon Adolescents - Bhadauria, Mridula; Gore, Rashmi; Pandey, Dheeraj (INDIAN EDUCATIONAL REVIEW, 2011)
The present study was conducted to find out the effect of excessive use of internet upon adolescents, mental health. The major findings of the study were : (i) Internet usage negatively affects the mental health of adolescents. (ii) Internet usage affects more to the mental health of rural adolescents than that of urban adolescent. (iii) Internet usage affects the mental health of adolescent boys and girls of different SES same way. (iv) Internet usage and area differences are interacting significantly for the adolescents mental health and no variable are interacting significantly with one another for the mental health of adolescents.